Pharmacokinetics of orally administered oseltamivir in healthy obese and nonobese thai subjects - Jittamala, P; Pukrittayakamee, S; Tarning, J; Lindegardh, N; Hanpithakpong, W; Taylor, W; Lawpoolsri, S; Charunwattana, P; Panapipat, S; White, N; Daya, N (2014)
Oseltamivir is the most widely used anti-influenza drug. In the 2009 H1N1 pandemic, in which the influenza viruses were oseltamivir sensitive, obesity was identified as a risk factor for severe disease and unfavorable outcomes. The aim of this study was to investigate the pharmacokinetic properties of oseltamivir and its active metabolite, oseltamivir carboxylate, in obese and nonobese healthy subjects. A single-dose, randomized, two-sequence crossover study was conducted in 12 obese and 12 nonobese healthy Thai volunteers. Each volunteer was given 75 mg and 150 mg oseltamivir orally with an intervening washout period of more than 3 days. The pharmacokinetic properties of oseltamivir and oseltamivir carboxylate were evaluated using a noncompartmental approach. The median (range) body mass indexes (BMIs) for obese subjects were 33.8 kg/m2 (30.8 to 43.2) and 22.2 (18.8 to 24.2) for nonobese subjects. The pharmacokinetic parameters of oseltamivir carboxylate, the active metabolite of oseltamivir, were not significantly different between obese and nonobese subjects for both 75-mg and 150-mg doses. Both doses were well tolerated. Despite the lower dose per kilogram body weight in obese subjects, there was no significant difference in the exposure of oseltamivir carboxylate between the obese and nonobese groups. Standard dosing is appropriate for obese subjects. (The study was registered at ClinicalTrials.gov under registration no. NCT 01049763.) Copyright © 2014 Jittamala et al.